EMPLOYEE PERFORMANCE IS VIEWED FROM SELF-EFFICACY, TEAMWORK, ORGANIZATIONAL CULTURE AND JOB SATISFACTION (Study at the Institute for The Development and Empowerment of Principals and Superintendents of Karanganyar Regency) - Erna Indawati; Bambang Mursito; Ida Aryati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this research is to find out the effect of a variable of self-efficacy, teamwork, organizational culture and job satisfaction on a variable called employee performance at LPPKSPS Karanganyar Regency. This research has been conducted using an approach called quantitative. The population in all employees who currently work at LPPKSPS Karanganyar Regency which has a total of 100 people. The sample technique used is simple random sampling technique with 50 respondents. Data were collected by questionnaire. The technique for analyzing the data of this research which has been used statistical analysis is multiple linear regression test. The results of the research that have been carried out have shown that a variable of self-efficacy, teamwork, organizational culture and job satisfaction has a positive and significant impact on a variable called employee performance at LPPKSPS Karanganyar Regency. Suggestions from this research, LPPKSPS Karanganyar Regency in the future will continue to maintain and improve the quality of self-efficacy, teamwork, organizational culture and job satisfaction, so that later it will continue to make employee performance will also continue to increase and of course be better than before. Keywords: Employee Performance, Self-Efficacy, Teamwork, Organizational Culture, Work Goals